Characterization of the gut microbiota and systemic inflammation in HIV-exposed uninfected infants from a resource-limited setting at 6 weeks of age - P. Munjoma; A. Mazhandu; J. Wyss; S. Ulrich Jordi; L. Katsidzira; B. Yilmaz; B. Misselwitz; K. Duri (Microbiota in Health and Disease)
Objective: Infants born to mothers infected with human immunodeficiency virus (HIV) experience heightened morbidity and mortality, likely due to systemic immune dysregulation potentially linked to gut microbial dysbiosis. However, the degree of variation in biomarkers and systemic inflammation between HIV-exposed uninfected (HEU) infants and their HIV-unexposed uninfected (HUU) peers remains uncertain.